User experience assessment on websites/mobile web apps (E-commerce) - Teo, Kian Boon (2017)
User Experience(UX) for E-Commerce is to rate how the user feel when they visit your website. It is also the experience of going through during a series of processes performed to reach their objectives. Poor UX Designs of website will generally leads to failure of E-Commerce Businesses due to the core concept of E-Commerce is built around its website. User Design Concepts (Chapter 2) mentioned that Users will ignore your webpage due to poor aesthetically look and if it gives user frustration, User will just switch to your competitor sites instead. This report will do a quick summary of some of the most important UX features needed for E-Commerce industry. User Experience Assessment (UXA) is to assess how good is your UX Design of your webpages. This report will also cover most of these techniques used in the UXA industry and their shortcoming (Chapter 2). Current UXA methods does not really tackle the reason behind why a UX Design for website is good or poorly done and provide the directions on improvement. With the shortcoming of current UXA techniques, there is a need for a new technique to solve this problem (Chapter 3). This project will introduce and focus on an all-new created UXA Technique known as User Experience Assessment Tiering Concept (UXA-TC) which is built on the very core of Good UX Design concepts (Chapter 4). UXA-TC will allow you to understand the root cause of why your website is poor/good in UX Design and show you the direction to improve it. UXA-TC will also help to access the risk and cost for implementing a new UX Features that you wish to add-on to your UX arsenals in your website. The report will then end off with a generic Guideline & Methodology (Chapter 5) to create good UX Design for your webpage and the future directions of UX.